Temperature measurements on a solar and low enthalpy geothermal open-air asphalt surface platform in a cold climate region - Çuhac, Caner; Mäkiranta, Anne; Välisuo, Petri; Hiltunen, Erkki; Elmusrati, Mohammed (MDPI, 2020)
Solar heat, already captured by vast asphalt fields in urban areas, is potentially a huge energy resource. The vertical soil temperature profile, i.e., low enthalpy geothermal energy, reveals how efficiently the irradiation is absorbed or radiated back to the atmosphere. Measured solar irradiation, heat flux on the asphalt surface and temperature distribution over a range of depths describe the thermal energy from an asphalt surface down to 10 m depth. In this study, those variables were studied by long-term measurements in an open-air platform in Finland. To compensate the nighttime heat loss, the accumulated heat on the surface should be harvested during the sunny daytime periods. A cumulative heat flux over one year from asphalt to the ground was 70% of the cumulative solar irradiance measured during the same period. However, due to the nighttime heat losses, the net heat flux during 5 day period was only 18% of the irradiance in spring, and was negative during autumn, when the soil was cooling. These preliminary results indicate that certain adaptive heat transfer and storage mechanisms are needed to minimize the loss and turn the asphalt layer into an efficient solar heat collector connected with a seasonal storage system.
Keywords: asphalt solar collector; heat flux; distributed temperature sensing; low enthalpy geothermal energy; renewable energy; soil temperature profile; temperature; heat energy; heat transfer; carbon dioxide; measurement; geothermal energy; energy; solar collectors; solar heating; heating systems; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|